PENERAPAN PEMENUHAN HAK RESTITUSI TERHADAP ANAK KORBAN TINDAK PIDANA KEKERASAN DEMI KEPASTIAN HUKUM - Tarigan, Diego Pratana; Shodiq, MD; Ismed, Mohamad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Child Victims of Violence are entitled to Restitution for the loss of a crime, The legal application of the fulfillment of the Right to Restitution has been proven in the decision of the panel of judges, in the implementation of the restitution charged, the perpetrator cannot pay restitution, Restitution is regulated by Law No. 35 of 2014 concerning Child Protection, Government Regulation No. 43 of 2017 concerning the Implementation of Restitution for Children who are Victims of Crime. The legal theories used are Legal Certainty Theory and Child Protection Theory. The research method used in this research is a normative juridical approach which is carried out as an effort to obtain the necessary data related to the problem. Data used with secondary data and tertiary legal materials. In addition, primary data is also used as a supporter of secondary data legal materials. For data analysis, a qualitative juridical analysis method is used. The results of the study that the application of the law to fulfill the restitution rights of child victims of violence in the form of a judge's decision in this case the perpetrator is unable to make restitution payments, therefore from the results of further research the legal rules for fulfilling restitution rights need to be revised to add phrases contained in article 21 of the regulation.